2018
DOI: 10.7150/thno.25433
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Cu-TCPP MOF nanosheets: a new theragnostic nanoplatform with magnetic resonance/near-infrared thermal imaging for synergistic phototherapy of cancers

Abstract: Nanostructures based on metal-organic frameworks (MOFs) have promising potential as theragnostic nanoplatforms for phototherapy of cancer cells. However, the MOFs alone are seldom reported to be used as photothermal agents mainly due to their poor near-infrared (NIR) light absorption.Methods: Ultrathin copper-tetrakis (4-carboxyphenyl) porphyrin (Cu-TCPP) MOF nanosheets were prepared by a facile solvothermal route. The photothermal therapy (PTT), photodynamic therapy (PDT), and T1-weighted magnetic resonance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(111 citation statements)
references
References 34 publications
4
104
0
3
Order By: Relevance
“…Wu et al. reported ultrathin 2D Cu‐TCPP MOF nanosheets for dual‐mode imaging‐guided phototherapy [67] . The Cu 2+ nodes in Cu‐TCPP nanosheets offered excellent photothermal properties for PTT, PTI, and T 1 ‐weighted MRI.…”
Section: Biomedical Applications Of Porphyrin‐based Mofsmentioning
confidence: 99%
“…Wu et al. reported ultrathin 2D Cu‐TCPP MOF nanosheets for dual‐mode imaging‐guided phototherapy [67] . The Cu 2+ nodes in Cu‐TCPP nanosheets offered excellent photothermal properties for PTT, PTI, and T 1 ‐weighted MRI.…”
Section: Biomedical Applications Of Porphyrin‐based Mofsmentioning
confidence: 99%
“…These 2D MOF nanosheets showed a notable synergistic antitumor effect in vivo and efficient biodegradation and rapid renal clearance behaviors. In addition, Li et al demonstrated that Cu‐TCPP nanosheets are promising phototherapy nanoplatforms guided by MR imaging for achieving the combined PDT‐PTT treatment of cancer with significantly improved treatment efficacy (Figure B) . Recently, Lin and co‐workers reported Hf‐BPY‐Ir and Hf‐BPY‐Ru nanosheets as photosensitizers for highly effective X‐ray‐induced PDT of cancer .…”
Section: D Metal–organic Frameworkmentioning
confidence: 99%
“…B) Ultrathin Cu‐TCPP MOF nanosheets for MRI and infrared thermal imaging‐guided PTT/PDT. Reproduced with permission . Copyright 2018, Ivyspring International Publisher.…”
Section: D Metal–organic Frameworkmentioning
confidence: 99%
“…Under irradiation with NIR light, the photothermal agent converts light energy into heat energy and induces cell apoptosis by utilizing the sensitivity of cells to heat. When PTT and PDT are combined, PTT can enhance PDT because the rate of PS‐induced 1 O 2 production is significantly increased at elevated temperatures …”
Section: Combined Theranostic Strategiesmentioning
confidence: 99%